Iqbāl dušmanī - Ṣābir, Aiyūb (Arīb Pablīkešanz, 2021)
Criticism of the poetry of Sir Muḥammad Iqbāl, 1877-1938; Urdu and Persian poet.
Der Paralleltitel ist eine Umschrift von der Rückseite der Haupttitelseite
Keywords: Hochschulschrift; Iqbal; Muhammad; Sir; 1877-1938; Criticism and interpretation.